Interneuronal exchange and functional integration of synaptobrevin via extracellular vesicles - Vilcaes, A. Alejandro (Neuron, 2021)
Recent studies have investigated the composition and functional effects of extracellular vesicles secreted by variety of cell types. However, the mechanisms underlying the impact of these vesicles on neurotransmission remain unclear. Here, we isolated extracellular vesicles secreted by rat and mouse hippocampal neurons and found that they contain synaptic vesicle-associated proteins, in particular the vesicular SNARE (soluble NSF-attachment protein receptor) synaptobrevin (also called VAMP). Using a combination of electrophysiology and live-fluorescence imaging, we demonstrate that this extracellular pool of synaptobrevins can rapidly integrate into the synaptic vesicle cycle of host neurons via a CD81-dependent process and selectively augment inhibitory neurotransmission as well as specifically rescue neurotransmission in synapses deficient in synaptobrevin. These findings uncover a novel means of interneuronal communication and functional coupling via exchange of vesicular SNAREs.